A Self-Tunable Piezoelectric Energy Harvester - Hussein, Ashraf (AUC Knowledge Fountain, 2021)
In this study, a new technique to harvest energy using inertial vibration energy harvesters is introduced. A triple-layer piezoelectric beam with a self-tunable frequency was developed in order to respond to variable-frequency excitations, thereby maintaining the beam in a state of resonance for maximum power output. The tuning mechanism managed to change the natural frequency of the beam in the range of 2.27 to 6.25 . In this case, the output voltage could be raised from 12 to 23. A mathematical model was developed to investigate the natural frequency, the output voltage, and the output power of the beam in various tuning angles. Experimental readings of the natural frequency and the output voltage were recorded in various tuning angles. The mathematical results and the experimental results were compared together to confirm the validity of the model. The experimental work results were entirely accurate when compared with the mathematical model. Finally, a parametric study was performed to study the effect of changing the main systems parameters as the tuning masses, the tuning arm length, and length of the beam on the natural frequency. The impact of the load resistance on the output voltage was also studied as a part of this parametric study